Analisis Perancangan Sistem Ketidakhadiran Karyawan Berbasis Website Menerapkan Rapid Application Development - Evy Nurmiati; Fadhlan Yahya; Musthafa Kamil (Bulletin of Computer Science Research, 2025)
In the current era of rapid digital transformation, information systems play an essential role in enhancing the efficiency and operational effectiveness of any organization, which is the precise focus of this research conducted at the Central Indonesian Ulema Council (MUI). The study's objective was to design a website-based employee absence system to digitally streamline and facilitate the previously manual processes of submitting leave applications, permit requests, and resolving attendance issues. The core problems identified were significant delays in the administrative process and a heavy reliance on physical documents, leading to overall inefficiency and vulnerability. To address these critical challenges, the research utilized the Rapid Application Development (RAD) methodology, which strongly emphasizes speed of development and active user involvement across three main phases: requirements planning, system design, and prototype construction. The necessary data was gathered through direct field observation and informal interviews conducted with the Human Resource Development (HRD) department and employee representatives. The tangible outcome of this research is a functional web-based system prototype design that offers key features, including the ability to download application forms for leave requests, permit requests, and attendance problem forms digitally. This innovative system is expected to substantially increase the work effectiveness of the HRD team, drastically minimize the consumption of physical documents, and provide greater convenience and autonomy for all employees in accessing and obtaining the necessary administrative documents independently and promptly